Diagramas de manejo da densidade para povoamentos de Acacia mearnsii De Wild. - Finger, Anelisa Pedroso (2016)
Density management diagrams (DMD) is a tool used to carry out the prognosis of production in density, basal area and volume in order to establish management strategies for forest planning. The aim was to build a density management diagram for Acacia mearnsii De Wild. Data from 12 cities in the northeastern region of Rio Grande do Sul were used for the DMD construction. Since the Tang model had the best evaluation, it was used to select the maximum population density estimative, thus the density 1x1 was used to construction of the DMD. With the same model, self-thinning graphs and Stand Density Index (SDI) were generated; adopting a standard quadratic mean diameter of 10cm. Density levels were determined proportionally to SDI maximum density in 200 class intervals, with higher 2400 and lower 1400 SDI. The DMD were produced with an average diameter and density control, and volume and green rind bark weight per hectare. A second DMD model was developed in order to insert a site production control through the dominant height of the stand. These DMD models allowed estimating the volume and green rind bark with great precision, from the control of diameter, density and dominant height.